PENGARUH PERSEPSI MANFAAT, KEMUDAHAN DAN KEPERCAYAAN TERHADAP MINAT PENGGUNAAN QRIS - Siti Nazwa Ramadanti; Ruslinda Agustina; Rara Gustiana (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
The aim of the study was to empirically prove the effect of perceived benefits, ease of use, and trust on the interest in using QRIS among students of the Accounting Study Program at STIE Nasional Banjarmasin. The method used in this study was quaantitative method by distributing questionnaires to 41 participants of the Accounting Study Program at STIE Nasional Banjarmasin. This study utilizes SPSS software version 26.00. The conclusion of this study is that Perceived Benefits, Ease of Use, and Trust have both partial and simultaneous effects on the Interest in Using QRIS among students of the Accounting Study Program at STIE Nasional Banjarmasin.